The Impact of Real Government Spending in Physical and Social Infrastructures on Economic Growth - Purbo Nugroho; Sofyan Syahnur; Suriani Suriani (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2022)
Most countries in the world undertake to achieve a high and sustainable economic growth due to it represents the economic welfare of countries. This study aims to analyze the effect of government spending in the physical and social infrastructures on economic growth, particularly in Indonesia by using secondary panel data 33 provinces during the period 2005-2018. Theoretically, usual economic growth model is highly affected by capital with flow characteristics. This study employs the capital stocks divided by physical and social infrastructures (public goods) consisting of Road and Bridge (BR), Irrigation, airport, port, health, and educational infrastructures as dominant variables. This study uses Panel ARDL model to investigate the functional relationship of economic growth and the public capital stocks in the short-term and long-term. The results show that all variables show a negative effect, except the road and bridge (RB) has a significant effect on economic growth in the short term. In the long term, roads and bridges (RB) and irrigation channel (IC) have a positive and significant effect on economic growth, but the others are not. These results are supported by the Pedroni Cointegration Test and KAO Cointegration Test which show a short-term and long-term balance. These findings underline that public infrastructure as capital stocks of each region with the appropriate infrastructure development play important role in sustaining the economic growth in Indonesia.